Protocol for an Effectiveness-Implementation Hybrid Trial to Evaluate Scale up of an Evidence-Based Intervention Addressing Lifestyle Behaviours From the Start of Life: INFANT - Laws, Rachel; Love, Penelope; Hesketh, Kylie D.; Koorts, Harriet; Denney-Wilson, Elizabeth; Moodie, Marj; Brown, Vicki; Ong, Kok-Leong; Browne, Jennifer; Marshall, Sarah; Lioret, Sandrine; Orellana, Liliana; et al. (Frontiers in Endocrinology, 2021)
Introduction: Promoting healthy eating and active play in early life is critical, however few interventions have been delivered or sustained at scale. The evaluation of interventions at scale is a crucial, yet under-researched aspect of modifying population-level health behaviours. INFANT is an evidence-based early childhood healthy lifestyle intervention that aims to improve parents’ knowledge and skills around promoting optimal energy balance-related behaviours that, in turn, influence children’s diet, activity and adiposity. It consists of: 1) Four group sessions delivered via first time parent groups across the first 12 months of life; 2) access to the My Baby Now app from birth to 18 months of age. This research aims to assess real-world implementation, effectiveness and cost-effectiveness of INFANT when delivered at scale across Victoria, Australia. Methods and analysis: A hybrid type II implementation-effectiveness trial applying a mixed methods design will be conducted. INFANT will be implemented in collaboration with practice and policy partners including maternal and child health services, population health and Aboriginal health, targeting all local government areas (n=79) in Victoria, Australia. Evaluation is based on criteria from the ‘Outcomes for Implementation Research’ and ‘RE-AIM’ frameworks. Implementation outcomes will be assessed using descriptive quantitative surveys and qualitative interviews with those involved in implementation, and include intervention reach, organisational acceptability, adoption, appropriateness, cost, feasibility, penetration and sustainability. Process measures include organisational readiness, fidelity, and adaptation. Effectiveness outcomes will be assessed using a sample of INFANT participants and a non-randomised comparison group receiving usual care (1,500 infants in each group), recruited within the same communities. Eligible participants will be first time primary caregivers of an infant aged 0-3 months, owning a personal mobile phone and able to communicate in English. Effectiveness outcomes include infant lifestyle behaviours and BMIz at 12 and 18 months of age. Impact: This is the first known study to evaluate the scale up of an evidence based early childhood obesity prevention intervention under real world conditions. It has the potential to provide generalisable implementation, effectiveness and cost-effectiveness evidence to inform the future scale up of public health interventions both in Australia and internationally.